Pengaruh Minat Belajar Peserta Didik terhadap Hasil Belajar Matematika - Dian Purnama Sari (Tunas Nusantara, 2023)
In general, mathematics is often seen as difficult by studennts. Thus it be seen from the learning outcomes most of them do not meet the minimum completeness criteria of the school. Of course there are many obstacles including students' learning interest. The purpose of this study is to understand the influence of Pesdik's learning interests on the mathematics learning outcomes of V-B class students at SD Negeri Purwoyoso 04 Semarang. This research is included in quantitative research with data collection carried out using a questionnaire to find out students' learning interests and tests related to students' mathematics learning outcomes. The technique of data analysis is regression analysis. The results showed that there was a significant influence between learning interest and students' mathematics learning outcomes. Thus it is evident from the calculation results which show a significance of 0.043 <0.05. It can be concluded that there is an influence of interest in learning on the learning outcomes of students in mathematics.